Facile one-step synthesis of porous graphene-like g-C3N4 rich in nitrogen vacancies for enhanced H2 production from photocatalytic aqueous-phase reforming of methanol. (1st January 2021) - Wang, Ruiyi; Wang, Xiaoyu; Li, Xincheng; Pei, Linjuan; Gu, Xianmo; Zheng, Zhanfeng
Abstract: Exfoliation of bulk graphitic carbon nitride (g-C3 N4 ) to single- or few-layered structures is an effective way to improve the photocatalytic performance. However, the synthesis methods for few-layer g-C3 N4 are relatively complicated and time-consuming, with the bandgap of g-C3 N4 increasing through quantum size effects, thus hampering effective utilization of visible light. To effectively exfoliate the bulk g-C3 N4 to single or few-layered structures in a facile way without losing its visible light absorption ability is still a challenge. Herein, porous graphene-like g-C3 N4 nanosheets with abundant nitrogen vacancies were prepared by facile thermal polymerization of melamine using graphene oxide (GO) as a sacrificial template. The two-dimensional (2D) layer morphology and nitrogen defect structure were proved using AFM, SEM, TEM, EA, XPS and EPR techniques. Compared with the bulk g-C3 N4, the as-prepared g-C3 N4 nanosheet possesses a high specific surface area, enhanced absorption ability of visible light, and elevated charge carrier generation and separation efficiency because of the unique structural features. The in situ DRIFT spectrum indicates that the surface nitrogen vacancies also serve as excellent locations for methanol adsorption and activation. Consequently, an excellent photocatalytic activity of hydrogen production from methanol aqueous-phase reforming is obtained, which is about 14 times more productive than the bulk g-C3 N4 . Graphical abstract: Graphene-like porous few layer g-C3 N4 nanosheets exhibit excellent photocatalytic performance for hydrogen production by methanol photoreforming under visible light irradiation, owing to the nanosheets possessing abundant nitrogen vacancies, high specific surface area, enhanced visible light absorption, and efficient electron-hole pair generation and separation. Image 1 Highlights: Nitrogen defective porous g-C3 N4 can be obtained using graphene oxide as template. The nitrogen vacancies enhanced photoexcited charges generation and separation. A 14-fold increase of the hydrogen production rate was realized.